Punch-drunk love - Revolution Studios ([s.l.] Revolution Studios, 2003)
This misfit love story of disconnected people trying to find one another in an antagonistic world is a comedy of discomfort and rage that turns unexpected sweet and pure.
VCD
Produced by Joanne Sellar, Daniel Lupi, Paul Thomas Anderson ; written and directed by Paul Thomas Anderson.
Adam Sandler, Emily Watson
Keywords: Comedy--Feature.; Romance--Feature.